Overcoming the abnormal grain growth in Ga-doped Li7La3Zr2O12 to enhance the electrochemical stability against Li metal. Issue 12 (15th August 2019) - Su, Jianmeng; Huang, Xiao; Song, Zhen; Xiu, Tongping; Badding, Michael E.; Jin, Jun; Wen, Zhaoyin
Abstract: Li7 La3 Zr2 O12 (LLZO) solid electrolyte is a promising candidate for next generation batteries. In the LLZO family with various doping elements, Ga-doped LLZO (Ga-LLZO) delivers the highest Li-ion conductivity of higher than 1 × 10 −3  S cm −1 . However, Ga-LLZO ceramics always contain lots of overgrown huge grains after sintering, resulting in short-circuiting as applied with Li anode in batteries. Hence a simple two-step sintering strategy is developed to prepare fine-grained Ga-LLZO ceramics with good electrochemical properties. Pellets with the composition of Li6.4 Ga0.2 La3 Zr2 O12 deliver pure garnet phase, uniform fine grains, high relative density of 97.3% and conductivity of 1.24 × 10 −3  S cm −1  at 27 °C after sintering at 1150 °C for 1 min and 1000 °C for 3 h. In addition, those fine-grained Ga-LLZO exhibit improved stability against molten Li. The Li/Ga-LLZO/Li symmetric cells show a critical current density of 0.7 mA cm −2, and a stable cycling of over 600 h at 0.4 mA cm −2  at 27 °C. The Li/Ga-LLZO/LiFePO4 full cells deliver reversible capacity of 150 mAh g −1, showing negligible decay after 50 cycles. These results bring the Ga-LLZO electrolytes one step closer to practical application in solid-state batteries.